Distribution of hyaluronidase-producing staphylococcus aureus and staphylococcus epidermidis isolated from palm skin and anterior nares of healthy Malaysian adults - Abdul Halim, Nabila Huda; Mohd Zahir, Nur Syarafina; Mohd Amin, Nor Munirah; Ahmad Yusof @ Hanafi, Hanani (Faculty of Medicine, Universiti Teknologi MARA, 2020)
Introduction: The distribution of Staphylococcus aureus and Staphylococcus epidermidis among Malaysian healthy adults and their capability to produce enzyme hyaluronidase are less reported. Hyaluronidase degrade hyaluronic acid in animal connective tissue and facilitate bacterial spreading in host body. This study aims to identify the distribution of both Staphylococci species in healthy subject, the hyaluronidase producer among the isolates and the association of the latter with site of isolation (palm skin and anterior nares) and gender of the host. Methods: A total of 108 swab samples were collected from anterior nares and palm of 54 healthy subjects. The bacteria were identified through microscopic and biochemical tests, before screened for hyaluronidase production using hyaluronic acid diffusion rapid plate method. Results: Total of 139 bacterial isolates were identified; 68 isolates are S. aureus, 63 S. epidermidis and 8 other bacterial species. Staphylococcus aureus was highly isolated from palm (57%) than anterior nares (47%). On the contrary for S. epidermidis was highly isolated from anterior nares (53%) than from palm skin (43%). Equal proportion was found for both species in male and female subject. A total of 77 (59%) isolates produced hyaluronidase; 55% are S. aureus and 45% are S. epidermidis. Hyaluronidase-producer isolates are equally found between anterior nares (56%) and palm skin (61%) or male (57%) and female subject (60%) regardless of Staphylococcal species. No significant value was recorded for any analysis. Conclusion: Capability of commensal S. aureus and S. epidermidis isolated from healthy subject to produce hyaluronidase may indicate their potential as opportunistic pathogen whenever the opportunity arises in any way.